Pengembangan Media Pembelajaran Animasi Berbasis Animaker dalam Struktur Teks Negosiasi Siswa Kelas X SMA Swasta Nurul Islam Indonesia Medan - Meidiana Batubara; Deliani; Nila Safina; Ratna Soraya (Medan Resource Center, 2022)
This study aimed to describe the development process and feasibility of animation learning media based on animaker in class X SMA Nurul Islam Indonesia Medan. The source of data is a questionnaire. The data collection techniques used observation and interviews to gain data in learning the structure of negotiating texts. This study used research and development (R&D) by Thiagajaran that consists of 4 stages of development; 1)definition stage, 2)design stage, 3)development and 4)dissemination. The researchers tested the product in large and small groups. The material expert validation of the developed animaker-based animation learning media obtained an overall average as 78% or